REINFORCING LEGACY BRAND: TRANSFORMING CONSUMER PERCEPTIONS THROUGH BRAND STRATEGIES IN THE TOBACCO INDUSTRY - Putra Sudja, Mario; Wibowo, Satya Aditya; Windasari, Nila Armelia (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
This study investigates brand strategies for sustaining the relevance of legacy brands in Indonesia’s highly regulated and socially sensitive tobacco industry. The focus is on Djarum Super, an iconic kretek cigarette brand with a historically loyal customer base that is currently struggling to connect with younger consumers. A qualitative case study approach was used, combining in-depth interviews, projective techniques, and digital ethnography to explore consumer perceptions, brand associations, and behavioral tendencies. The research engaged 15 male respondents aged 21–35 from urban areas, selected based on smoking behavior and socioeconomic profile. The analysis applied Keller’s Customer-Based Brand Equity (CBBE) framework and thematic content analysis to identify the brand’s current positioning and consumer resonance. Findings reveal a clear generational divide: older consumers demonstrate attachment based on nostalgia, cultural pride, and masculine identity, while younger consumers perceive the brand as outdated, harsh in flavor, and disconnected from modern lifestyles. The study highlights the need for revitalizing brand salience through updated visual identity, emotionally driven storytelling, and culturally relevant messaging. Moreover, digital co-creation and community-based marketing are proposed to foster engagement without violating advertising restrictions. This repositioning should aim to reframe the brand’s image not by abandoning its heritage but by reshaping it into a more inclusive and aspirational narrative. The study contributes practical insights for brand managers navigating generational shifts, consumer perception gaps, and strict regulatory environments. It also offers a strategic model for legacy brands attempting to bridge tradition with innovation in evolving consumer landscapes.